Modernist Soundscapes : Auditory Technology and the Novel - Frattarola, Angela (Book collections on Project MUSE., 2018)
This study questions how early twentieth-century auditory technologies altered sound perception, and how these developments shaped the modernist novel. Without polarizing vision and audition, this book reveals how modernists tend to use auditory perception to connect characters, shifting the subject from a distanced, judgmental observer to a reverberating body, attuned to the moment.